Estimado del costo de apoyo institucional para asociaciones procesadoras de yuca en la Costa Norte de Colombia - Romanoff, S.A. (International Center for Tropical Agriculture, 1985)
The institutional costs involved in the promotion and development of cassava processing plants on the Northern Coast of Colombia are presented, and the implication that these might have on future plans is analyzed and discussed. (CIAT)